2008
DOI: 10.1002/bit.21829
|View full text |Cite
|
Sign up to set email alerts
|

Protopanaxadiol 6‐hydroxylase and its role in regulating the ginsenoside heterogeneity in Panax notoginseng cells

Abstract: Various structure-similar plant secondary metabolites like ginseng saponins (ginsenosides) possess different or even totally opposite biological activities. Intentional manipulation of the ginsenoside heterogeneity in cellular biosynthesis is of great interest and significance [Zhong and Yue (2005); Adv Biochem Eng Biotechnol 100:53-88]. In this work, CO-binding spectra of microsomes prepared from the suspended cells of Panax notoginseng showed increases in absorption at 450 nm compared with the control withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Two triterpene aglycons, protopanaxadiol and protopanaxatriol, were synthesized by the consecutive reaction of dammarenediol 12-hydroxylase (D12H) and protopanaxadiol 6-hydroxylase (P6H), respectively. These enzymes responsible for hydroxylation were putatively Recently, P6H enzyme, which catalyzes the biosynthesis of protopanaxatriol from protopanaxadiol, has been identified using microsomal proteins of P. notoginseng cell suspension cultures (Yue et al 2008). Hu and Zhong (2007) have revealed that the P6H activity was increased with MJ exposure time in cell suspension cultures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two triterpene aglycons, protopanaxadiol and protopanaxatriol, were synthesized by the consecutive reaction of dammarenediol 12-hydroxylase (D12H) and protopanaxadiol 6-hydroxylase (P6H), respectively. These enzymes responsible for hydroxylation were putatively Recently, P6H enzyme, which catalyzes the biosynthesis of protopanaxatriol from protopanaxadiol, has been identified using microsomal proteins of P. notoginseng cell suspension cultures (Yue et al 2008). Hu and Zhong (2007) have revealed that the P6H activity was increased with MJ exposure time in cell suspension cultures.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is currently no genetic information available regarding the next step in ginseng, possibly hydroxylation or glycosidation. Recently, protopanaxatriol has been successfully biotransformed from protopanaxadiol using microsomal proteins evidencing protopanaxadiol 6-hydroxylase (P6H) activity (Yue et al 2008). Choi et al (2005) have reported that the EST (expressed sequence tag) data of this plant and the candidate genes encoding for cytochrome P450-dependent hydroxylase and glucosytransferase have been selected.…”
Section: Introductionmentioning
confidence: 99%
“…PDMOs mediate the oxidation of inert methylene and methyl groups of triterpene skeletons [60,61]. They include several concrete enzymes, for example, protopanaxadiol hydroxylase (P6H) which catalyzes the biosynthesis of protopanaxatriol from protopanaxadiol [62], and cytochrome P 450 -dependent hydroxylase [63] NADPH and O 2 , and that the enzymatic reaction was inhibited by carbon monoxide, was partially reversible upon illumination with blue light, and sensitive to cytochrome P 450 inhibitors [62].…”
Section: Key Enzymes Of Triterpenoid Saponin Biosynthesismentioning
confidence: 99%
“…In 2008, protopanaxadiol 6‐hydroxylase (P6H), a new enzyme catalyzing the conversion of ginsenoside aglycone protopanaxadiol into protopanaxatriol was found by Yue et al. . In 2012, Han et al.…”
Section: Analysis Of Ginsenoside Biosynthetic Pathwaymentioning
confidence: 99%
“…At present, more than 40 genes encoding ginsenoside biosynthesis related enzymes have been cloned and identified from Panax genus, and the basic biological elements have been provided for the production of ginsenosides by biosynthesis, which laid a good foundation for the study. In 2008, protopanaxadiol 6-hydroxylase (P6H), a new enzyme catalyzing the conversion of ginsenoside aglycone protopanaxadiol into protopanaxatriol was found by Yue et al [43]. In 2012, Han et al [2] identified CYP716A47 from ginseng to catalyze the synthesis of protopanaxadiol (PPD) at the C-12 hydroxylation of dammarane; CYP716A53v2 catalyzes the further synthesis of protopanaxadiol (PPT) through C-6 hydroxylation of PPD.…”
Section: Analysis Of Ginsenoside Biosynthetic Pathwaymentioning
confidence: 99%